Perampanel increases seizure threshold in pentylenetetrazole-kindled mice and improves behavioral dysfunctions by modifying mRNA expression levels of BDNF/TrkB and inflammatory markers - Nadia Perveen; Faleh Alqahtani; Waseem Ashraf; Muhammad Fawad Rasool; Syed Muhammad Muneeb Anjum; Iram Kaukab; Tanveer Ahmad; Saleh A. Alqarni; Imran Imran (Elsevier, 2024)
Perampanel (PER), a novel 3rd-generation antiseizure drug that modulates altered post-synaptic glutamatergic storming by selectively inhibiting AMPA receptors, is recently approved to treat intractable forms of seizures. However, to date, presumably consequences of long-term PER therapy on the comorbid deleterious psychiatric disturbances and its correlation with neuroinflammatory parameters are not fully investigated in chronic models of epilepsy. Therefore, we investigated the real-time effect of PER on brain electroencephalographic (EEG) activity, behavioral alterations, redox balance, and relative mRNA expression in pentylenetetrazole (PTZ) induced kindling. Male BALB/c mice were pretreated with PER (0.125, 0.25, and 0.5 mg/kg) for 3 weeks and challenged with 11 injections of PTZ at the sub-threshold dose of 40 mg/kg every other day. vEEG from implanted cortical electrodes was monitored to elucidate seizure propagation and behavioral manifestations. Recorded EEG signals exhibited that PER 0.5 mg/kg pretreatment exceptionally impeded the onset of sharp epileptic spike-wave discharges and associated motor symptoms. Additionally, qEEG analysis showed that PER prevented alterations in absolute mean spectral power and reduced RMS amplitude of epileptogenic spikes vs PTZ control. Furthermore, our outcomes illustrated that PER dose-dependently attenuated PTZ-evoked anxiety-like behavior, memory deficits, and depressive-like behavior that was validated by a series of behavioral experiments. Moreover PER, significantly reduced lipid peroxidation, AChE, and increased levels of SOD and total thiol in the mice brain via AMPAR antagonism. Post-PTZ kindling provoked overstimulation of BDNF/TrkB signaling and increased release of pro-inflammatory cytokines that were reversed by PER with suppression of iNOS in brain immune cells. In conclusion, our findings highlight that PER might play an auspicious preventive role in the proepileptic transformation of brain circuits via suppression of BDNF/TrkB signaling and reduced transcriptional levels of neuroinflammatory markers leading to improvised epilepsy-induced neurobehavioral and neurochemical effects.